Distribuição geográfica e diversidade de passalidae (Coleoptera: Scarabaeoidea) no sudeste da Mata Atlântica (Brasil). Geographic Distribution and Diversity of Passalidae (Coleoptera: Scarabaeoidea) from the Atlantic Rainforest of Southeastern (Brazil). - Mattos, Ingrid; M. Mermudes, José Ricardo (Instituto de Ecología, A.C., 2015)
RESUMO. A fauna de Passalidae é pouco conhecida no Sudeste do Brasil, uma região com domínio de Mata Atlântica que inclui uma fitofisionomia tropical típica da costa brasileira, com elementos distintos de geologia e geografia. O estudo foi conduzido em sete unidades de conservação do bioma de Mata Atlântica e forneceu uma lista das espécies de Passalinae com mapas de distribuição dos gêneros para a região Sudeste. A diversidade de Passalidae do Sudeste do Brasil incluiu 44 espécies, das quais 37 apresentam registros nas áreas de conservação com base no material coletado que recuperou 30 espécies. Passalus (Pertinax) convexus Dalman, 1817, Passalus (Passalus) denticollis  Kaup, 1869 e Passalus (Passalus) punctiger Lepeletier &Serville, 1825 foram as espécies mais abundantes, representando 49% dos indivíduos coletados. Passalus (Pertinax) convexus é a espécie mais abundante no bioma do Sudeste. Com base em uma ampla amostra de material examinado de diversas instituições, assinalamos 25 novas localidades, sendo 11 novos registros para estados do Brasil e sete registros para outros países da América do Sul, promovendo acréscimos para a distribuição das espécies do Sudeste do Brasil. Passalus nasutus  Percheron, 1835 tem novos comentários taxônomicos para elucidar um problema com Passalus (Passalus) curtus Kaup, 1869, onde o primeiro é restrito ao Brasil e o segundo a Colômbia. ABSTRACT. The Passalidae fauna is poorly known in the southeasternof Brazil, a region with Atlantic Forest thatincludes typical tropical phyto-physiognomies of the Brasilian coast, with distinctive geology and geography. This is the first study in seven areas of conservation of the Atlantic Forest of Southeastern Brazil, and intends to list the species of Passalinae. Actually, the diversity of Passalidae fauna from southeastern of Brazil increase to 44 species, of which 30 were collected and are accurately recorded in remnants of Atlantic Forest biome. Passalus (Pertinax) convexus Dalman, 1817, Passalus (Passalus) denticollis Kaup, 1869 and Passalus (Passalus) punctiger Lepeletier & Serville, 1825 were the most abundant, representing over 49% of individuals. Passalus (Pertinax) convexus is one of the most typical species from the Atlantic Forest biome in the Southeast. Based on a large sample of material examined from several institutions, we found 25 new locations, 11 new records for the states of Brazil and seven records to other countries in South America, promoting additions to the distribution of species in Southeast Brazil. Passalus nasutus Percheron, 1835 have new unambiguous comemmts to elucidate Passalus (Passalus) curtus Kaup, 1869, where the former species is restricted to Brazil and the latter is restricted to Colombia.